MATHEMATICAL INNOVATION: TEACHING PRACTICE IN SOLVING 2ND GRADE EQUATIONS IN HIGH SCHOOL - Martins Lopes, Rivanaldo (Journal of Interdisciplinary Debates, 2023)
The practice of finding the roots of a 2nd degree equation in current high school has been presented as a tool that makes learning and practice difficult for students and teachers. In this context, the present work aims to present innovative teaching, a tool used to find the roots of a quadratic equation without the use of formulas, with the aim of improving the level of difficulty in learning this content for high school students. To achieve the objectives proposed in this work, a bibliographical survey of the subject was carried out in the Scielo and Google Scholar databases, comprising a literary window from 400 BC to 2023. In addition, a qualitative-quantitative methodology was used, with random variables discreetly, it was applied to 118 students from ECI Dorgival Silveira in the city of São Francisco PB with an experiment via problems in determining the solution and its data were analyzed based on descriptive statistics. Within this study, it was possible to observe that this teaching is practical in solving the difficulties and challenges experienced by basic education students and teachers. For this, we can have other researchers who can continue this study as relevant as the ways of finding the right solution for students in contemporary times.